Evaluation Of Post Traumatic Stress Disorder And Its Complications - Srinivasan P; Jeevanandham S.; Deepak Krishnan L K; Divagar M; Faheem Kurikkal P; Farooque Ahammed C; Muhammed Ajmal N P (Journal of Advanced Zoology, 2023)
Post-traumatic stress disorder (PTSD) remains a widespread mental health challenge with profound consequences for people exposed to traumatic events. This review provides a comprehensive and critical appraisal of recent research on PTSD and sheds light on the complexities of its diagnosis, etiology, and treatment. The review includes a comprehensive analysis of the various methods used in PTSD research, including neurobiological, psychological, and sociocultural perspectives. It examines the impact of evolving diagnostic criteria and emphasizes the need to understand the nuances of symptoms and their heterogeneity in different populations. In addition, this summary discusses complications associated with PTSD research, such as comorbidities, cultural variations, and the influence of genetic factors. The interaction between trauma severity, resilience factors and the likelihood of developing chronic PTSD is explored, providing insight into the different trajectories observed in affected individuals. The review also discusses advances in therapeutic interventions, from traditional psychotherapeutic approaches to new pharmacological and neuromodulatory strategies. Special attention is given to the challenges of implementing evidence-based treatment and the need to tailor individualized treatments tailored to the unique needs of PTSD patients. Together, this summary summarizes the current state of PTSD research, highlights gaps in knowledge, and suggests avenues for future research. The complexity of PTSD research requires a multidimensional approach that integrates biological, psychological and sociocultural factors, ultimately contributing to a more comprehensive understanding of the disorder and improved treatment outcomes.